Parenteral Provision of Micronutrients to Pediatric Patients: An International Expert Consensus Paper. (4th September 2020) - Hardy, Gil; Wong, Theodoric; Morrissey, Hana; Anderson, Collin; Moltu, Sissel J.; Poindexter, Brenda; Lapillonne, Alexandre; Ball, Patrick A.
Abstract: Introduction: Micronutrients (vitamins and trace elements) are essential to all nutrition. For children and neonates who are dependent upon nutrition support therapies for growth and development, the prescribed regimen must supply all essential components. This paper aims to facilitate interpretation of existing clinical guidelines into practical approaches for the provision of micronutrients in pediatric parenteral nutrition. Methods: An international, interdisciplinary expert panel was convened to review recent evidence‐based guidelines and published literature to develop consensus‐based recommendations on practical micronutrient provision in pediatric parenteral nutrition. Results: The guidelines and evidence have been interpreted as answers to 10 commonly asked questions around the practical principles for provision and monitoring of micronutrients in pediatric patients. Conclusion: Micronutrients are an essential part of all parenteral nutrition and should be included in the pediatric nutrition therapy care plan.